Comparison of Hemiarthroplasty and Total Hip Arthroplasty in Elderly Patients with Displaced Femoral Neck Fractures - Muhammad Kamran Shafi, Muhammad Iqbal Buzdar, Shahid Mahmood, Mujtaba Afzal Khan, Faisal Mubeen (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Hemiarthroplasty (HA) and total hip arthroplasty (THA) are the two alternate surgical interventions required for displaced femoral neck fractures in elderly patients. Though THA is superior in certain aspects such as hip pain, reoperation rate and function but had higher dislocation rate compared to HA. The present study aimed to compare the hemiarthroplasty and total hip arthroplasty in elderly patients with displaced femoral neck fractures. Patients and Methodology: This retrospective cohort study was conducted on 20 displaced femoral neck fractures patients in the Department of Orthopedic QAMC/ BVH Bahawalpur from January 2021 to August 2022. Prior to start of study, ethical approval was taken from the institute research and ethical committee. Written informed consent was obtained from each individual. Patients aged >60 years and had femoral neck fractures were enrolled. Rheumatoid arthritis in fracture hip patients, non-ambulatory patients, and pathological fracture patients were excluded. Patients were categorized into two groups; group-I patients undergoing hemiarthroplasty and group-II patients undergoing total hip arthroplasty. Post-operative complications such as fracture, medical issues, dislocation, surgical site infection, and mortality (1 year) were assessed in both groups. Harris Hip Score (HHS) was used for the assessment of function outcome at one month, three months, six months, and twelve months. SPSS version 25 was used for data analysis. Results: Of the total 20 femoral neck fractures patients, 10 patients underwent hemiarthroplasty and 10 underwent total hip arthroplasty. The overall mean age was 69.44±7.91 years. Demographic details or baseline features were almost similar in both groups. During follow-ups, patients who underwent total hip arthroplasty (group-II) had higher Harris hip score than group-I patients. The mean HHS score in group-I patients were 61.53, 68.24, 70.81, and 76.16 at follow-up visit after one month, three months, six months, and twelve months respectively while In group-II, the mean HHS score were 66.23, 69.82, 73.25, and 78.92 respectively. Conclusion: Our study concluded that total hip arthroplasty in elder patients with femoral neck fractures provided better hip functional outcome and lower morbidity and mortality as compared to hemiarthroplasty group. THA could be considered as priority based treatment modality for femoral neck fractures patients than HA due to higher Harris hip scores and lesser complications. Keywords: Femoral neck fractures, Hemiarthroplasty, Total hip arthroplasty